Increased Productivity of Crops by Optimizing Parameters Buckwheat Sowing - Рарок, А. В.; Бурдига, В. М.; Коруняк, О. П. (Podilian Bulletin: Agriculture, Engineering, Economics, 2016)
Established that the productivity of crops of buckwheat depends in particular on parameters such as the rate and method of sowing seed. The research results showed that sowing parayetry affect the morphological structure of plant buckwheat varieties Malinka. In conventional string sowing plants were lower by 8-14 cm; less branched (1;2-1;9 pcs.); had fewer inflorescences (12;0-15;7 pcs.) аnd оzernenist plant was also poorer. Than the wide-sowing (45 cm) . On the morphological structure of plants; in addition to the method of sowing; and influenced by the different number of sown seeds per unit area. Yes; more productive plants were formed by conventional horizontal sowing seed rate of 4.2 million units. / Ha (63 pcs. / MP). 15.7 pc respectively small one. inflorescences and 23.7 pc. full of beans. For wide-seeding methods 30 and 45 cm morphostructures most productive plants of buckwheat respectively provided Calibration 2.4 million pcs. / Ha (71 pcs. / MP.) And 1.8 million pcs. / Ha (83 pcs. / MP). The optimum sowing buckwheat varieties Malinka conditions for the forest-steppe west; which improves the performance of biometric buckwheat plants and the formation of stable individual performance parameters are sowing with 4.2 million units. seeds / ha (15 cm); 2.4 million pcs. / Ha (30 cm) and 1.8 million pcs. / Ha (45 cm). The highest yield of buckwheat (1.68 t / ha) was achieved wideseeding (row spacing of 45 cm) and seeding rate of 1.8 million units. like seeds / ha.